Sinusoidal frequency doubler and full-wave rectifier using translinear current controlled conveyors - Anuntahirunrat, K.; Tangsrirat, W.; Riewruja, V.; Surakampontorn, W. (My University, 2000)
An alternative technique for realizing both a sinusoidal frequency doubler and a fall-wave rectifier, using translinear current controlled conveyors as active circuit elements, is presented. The frequency doubling and the rectifying action are exploited from the translinear characteristic of the current conveyor. Simulation results are given to confirm the theoretical predictions.